O sentido como acidente : as implicações estéticas da Library of Babel - Silva, Marcio Felipe da (2020)
The possibility of machines making works of art has fascinated mankind for centuries. Men have dreamed not only of machines equipped with a powerful artificial memory, capable of reproducing patterns and structures from previous texts; they have also devised machines capable of working on their own, producing beautiful works without any human input. The fact that written verbal language consists of nothing but visual symbols rearranged into meaningful structures makes this system (and Literature, as well) a field where experimentations with automated creation tend to be prolific. The interactive computer system Library of Babel, created by the American writer Jonathan Basile, based on the central metaphor of the short story “The Library of Babel”, by the Argentinian writer Jorge Luis Borges, is a remarkable techno-artistic product in this area. The system works on the mathematical principle of Combinatorics, so that any click on the refresh button triggers a different combination of 29 graphic symbols among all possible rearrangements, filling in a page with 3200 characters. As if in a lottery in which one wins by buying tickets for all possible rearrangements (which would evidently cost more than the prize), the system Library of Babel encompasses, under massive layers of linguistic chaos, all texts (literary or not) that could be written with these 29 graphic symbols. With that in view, this paper discusses the ontological and aesthetic consequences of a “total writing”, the logical premise of a project like the Library of Babel, which lies somewhere between a machine that subsumes all possible writers, but also all possible archives. As to the theoretical bases for our analysis, we will analyze Basile’s system from the perspectives defended by Umberto Eco (2012; 2016), Italo Calvino (2009; 1985), Maurice Blanchot (2013), Antoine Compagnon (2001), Roland Barthes (1998, 2007) and Julia Kristeva (1975).